Multiband antenna for body area network (BAN) - Ispawi, Dzufi Iszura (2012)
This project reports presents the design, simulation and measurement of a multiband antenna for Body Area Network (BAN). The objective is to produce a prototype antenna design that will work in two proposed frequency by FCC (Federal Communications Commissions) for BAN system. The antenna is using microstrip patch design and FR4 with dielectric constant 4.6 as its substrate. All the simulations results are obtained using CST Studio Suit Software. There are three antennas design produced by the end of the project and two of them achieved the project’s objective. Design B is able to work on 2.4 GHz and 3.7 GHz frequencies while Design C is able to work on 3.7 GHz and 5.2 GHz frequencies. Measurement process is done using a network analyser and the analysis for measurement and simulation results is discussed.